Pharmacoeconomic Analysis of Drugs Used in Chronic Outpatients at Berkah Pandeglang Regional Hospital - Yusransyah, Yusransyah; Nurhikmah, Ihda; Maharani, Zahra Citra; Stiani, Sofi Nurmay; Shobah, Afifah Nur; Udin, Baha (Sciences of Pharmacy, 2025)
Hypertension and type 2 diabetes mellitus (T2DM) are chronic conditions requiring long-term pharmacotherapy, placing significant financial pressure on patients and healthcare systems. Drug selection should prioritize both clinical efficacy and cost-efficiency, particularly in resource-limited settings. This study conducted a pharmacoeconomic evaluation of commonly used therapies at RSUD Berkah Pandeglang using a retrospective, non-experimental design. Data were collected from 2023 outpatient records and analyzed from the hospital’s perspective. Cost-effectiveness was assessed using the Average Cost-Effectiveness Ratio (ACER). For hypertension, amlodipine (n = 20) had a lower ACER (Rp 283,913) than candesartan (n = 15; Rp 883,000), indicating higher cost-effectiveness. In T2DM patients, metformin (n = 25) was more cost-effective (ACER: Rp 317,746.75) than glimepiride (n = 25; ACER: Rp 607,148.84). These findings support prioritizing amlodipine and metformin as first-line treatments in similar public healthcare settings to improve therapeutic outcomes while managing costs.